Observations on the Ingression and Distribution of Larval Prawns in the Nethravati-Gurupur Estuary, Mangalore - BRAT, B VISHNU; GUPTA, T. R CHANDRASEKHARA (Fishery Technology, 2017)
The spatial and temporal distributions of larval prawns of penaeids and non-penaeids in the estuarine waters of Mangalore were studied. Larvae appears to be passively brought in by the incoming flood tides to the estuary, enjoy a wider distribution throughout the estuarine complex with abundance towards the mouth. The distribution of larval prawns were more in Nethravati than in the Gurupur stretch. The influence of temperature, hydrogen-ion-concentration, salinity and dissolved oxygen on the distributtion of larvae in the estuaries is discussed. Inference on spawning seasons of commercially important prawns in the neighbouring waters has been arrived at based on their larval abundance.